Yield of upper gastrointestinal screening in colonic adenomatous polyposis of unknown etiology: a multicenter study - Farah, Filsan; Patel, Swati G.; Espinoza, Jeannine M.; Jensen, Nicholas; Katona, Bryson W.; Muller, Charles; Kupfer, Sonia S.; Weiss, Jennifer M.; Hinton, Alice; Stanich, Peter P. (Endoscopy International Open, 2022)
Background and study aims The majority of patients with 10 or more cumulative colorectal adenomas have uninformative genetic testing and meet criteria for colonic adenomatous polyposis of unknown etiology (CPUE). The yield of upper gastrointestinal screening in patients with CPUE after multi-gene panel testing is unknown and our objective was to characterize this. Patient and methods A multicenter, retrospective analysis of screening upper endoscopies in adults with CPUE after multi-gene panel testing was performed. Those with a history of gastroduodenal neoplasia prior to CPUE diagnosis were excluded. Demographic and clinical variables were collected and compared. Results One hundred and twenty-eight patients with CPUE were included from five participating centers. Nine (7.0 %) had gastroduodenal neoplasia on initial screening upper endoscopy. Those with over 100 colorectal adenomas had a significantly higher rate of gastroduodenal neoplasia than those with 20–99 or 10–19 colorectal adenomas (44.4 % vs 4.1 % vs 4.4 %, P = 0.002). Similar results were seen when the analysis was restricted to only duodenal or ampullary adenomas. The only malignancy was a gastric cancer in a patient with 20 to 99 colorectal adenomas. When comparing patients with gastroduodenal neoplasia to those without, the only significantly different characteristic was the cumulative number of colorectal adenomas.Conclusions We found a 7 % rate of gastroduodenal neoplasia in patients with CPUE after multi-gene panel testing. Although patients with ≥ 100 colorectal adenomas had a significantly higher risk, over 4 % of patients with 10 to 99 colorectal adenomas had gastroduodenal neoplasia. Given this, we recommend a screening upper endoscopy at the time of a colonoscopy after CPUE diagnosis.